2010
DOI: 10.1080/01634372.2010.516804
|View full text |Cite
|
Sign up to set email alerts
|

Grandparenting in the 21st Century: Issues of Diversity in Grandparent–Grandchild Relationships

Abstract: Although previous literature has demonstrated the importance of age, ethnicity, and socioeconomic status in understanding grandparent–grandchild relationships, additional factors contribute to a more complete and nuanced understanding of multigenerational relationships. Thorough understanding of the role of diversity requires examination of the discrete impacts of grandparents’ gender, sexual orientation, and physical and/or cognitive limitations on the relationship. This article focuses on these 3 important, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 80 publications
1
37
0
2
Order By: Relevance
“…Gender is an important theme in the research on grandparenthood (Dubas 2001;Leopold and Skopek 2015a, b;Stelle et al 2010;Szinovacz 1998;Uhlenberg and Hammill 1998). Grandmothers, and particularly maternal grandmothers, have longer overlap with grandchildren than grandfathers because of age differences between spouses compounded over two generations and sex differences in mortality (Hagestad and Lang 1986;Keck and Saraceno 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Gender is an important theme in the research on grandparenthood (Dubas 2001;Leopold and Skopek 2015a, b;Stelle et al 2010;Szinovacz 1998;Uhlenberg and Hammill 1998). Grandmothers, and particularly maternal grandmothers, have longer overlap with grandchildren than grandfathers because of age differences between spouses compounded over two generations and sex differences in mortality (Hagestad and Lang 1986;Keck and Saraceno 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a review of literature on the grandparent-grandchild relationship, Stelle (2010) concluded that one must consider the diversity and context in which the grandparent-grandchild relationship is embedded and lifelong patterns of family experiences, exchange, and attachment to understand contemporary intergenerational relationships (Stelle, 2010). It is evident that these contextual aspects formulated by Dr. Burton resonate today.…”
Section: Write Thatmentioning
confidence: 94%
“…We used a bioecological conceptual model (Tudge, Mokrova, Hatfield, & Karnick, 2009) to guide our research on the dynamics of intergenerational relationships, with youth viewed as embedded in the enduring reciprocal interactions of family, school, and community networks. This conceptual model is also highly compatible with interventions that are designed for a strengths-based perspective when working with multiple generations and respecting the diversity within the contexts of the grandchildgrandparent relationship (Stelle, Fruhauf, Orel, & Landry-Meyer, 2010).…”
Section: Introductionmentioning
confidence: 97%